Organic Chromium Form Alleviates the Detrimental Effects of Heat Stress on Nutrient Digestibility and Nutrient Transporters in Laying Hens - Orhan, Cemal; Tuzcu, Mehmet; Deeh, Patrick Brice Defo; Şahin, Nurhan; Komorowski, James R.; Şahin, Kazım (Humana Press Inc, 2019)
In the present study, we investigated the effects of chromium-picolinate (CrPic) and chromium-histidinate (CrHis) on nutrient digestibility and nutrient transporters in laying hens exposed to heat stress (HS). Hens (n=1800; 16weeks old) were kept in cages in temperature-controlled rooms at either 22 +/- 2 degrees C for 24h/day (thermoneutral (TN)) or 34 +/- 2 degrees C for 8h/day, from 08:00 to 17:00, followed by 22 degrees C for 16h (HS) for 12weeks. Hens reared under both environmental conditions were fed one of three diets: a basal diet and the basal diet supplemented with either 1.600mg of CrPic (12.43% Cr) or 0.788mg of CrHis (25.22% Cr) per kg of diet, delivering 200g elemental Cr per kg of diet. HS impaired the nutrient digestibility and nutrient transports in laying hens (P<0.001). However, both Cr sources increased digestibility of dry matter (DM; P<0.001), organic matter (OM; P<0.05), crude protein (CP; P<0.001), and crude fat (CF; P<0.001). Both Cr sources partially alleviated detrimental effects of HS on fatty acid-binding and transport protein1 (FABP1, FATP1), glucose (SGLT1, GLUT1, GLUT10), protein (PepT1, PepT2), and amino acid transporters (ASCT1, b(o,+)AT1, CAT1, EAAT1, LAT1) of the ileum (P<0.0001). The efficacy of Cr as CrHis was more notable than Cr as CrPic, which could be attributed to higher bioavailability. Finally, the detrimental effects of HS on nutrient digestibility and nutrient transporters were alleviated by CrPic and CrHis. These findings may justify the use of CrPic and CrHis in poultry.
Keywords: Chromium-histidinate; Chromium-picolinate; Digestibility; Nutrient transporters; Heat stress